Penentuan Kenaikan Jabatan Karyawan Menggunakan Metode Fuzzy-Analytical Hierarchy Process (FAHP) di Pabrik Gula Lestari Patianrowo Nganjuk - Erma Rafliza; Indriati Indriati; Rizal Setya Perdana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Career promotion is an important factor and heavily expected by the employees. Establishment of position that analyzed manually will be very disadvantage if there is Human Error or error conducted by humans related to the careful analysis towards the process compared to calculation conducted by machine. The implementation of Fuzzy-Analytical Hierarchy Process (FAHP) is conducted by determining matrix values of paired comparison as parameter about how important the parameter compared to other parameters. Three parameters as comparison are KIN (Individual Competence), KT (Core Competence), and KP (Role Competence). In this research, it used total test data of 78 which obtained result with accuracy level in the created system is 92.3%, in which matrix values of paired comparison as with expert statement, then if the level of importance for a parameter replaced to be slightly more important than value established by expert then accuracy level will be better, which is 94.87%. However, if the values established by expert replaced to be the opposite values then the obtained accuracy level is very low, which is only 79.48%. Therefore, although accuracy level by expert is already good, however, if a parameter changed to be slightly more important, then, the obtained result will be more optimal.